Penerapan Pembelajaran Berbasis Masalah dalam Pembelajaran Fikih untuk Mengajar Kemampuan Berpikir Kritis - Mohammad Balighudin (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
Islamic Religious Education learning, especially the subject of fiqh, has an important role in shaping students' understanding of Islamic laws. However, the conventional approach that is still often used is less able to attract students' interest in learning and is not optimal in building deep understanding. At MAN Pekalongan, these challenges are evident in the low learning outcomes of students and their weak critical thinking skills in understanding fiqh material. In response to these problems, the Problem Based Learning (PBL) approach is applied as an innovation in the learning process. This study aims to explore students' responses to the implementation of PBL and assess its effectiveness in improving understanding of fiqh and critical thinking skills. The method used in this study is a qualitative approach with data collection techniques in the form of interviews, observations, and document analysis. The results of the study show that PBL is able to create a more active, collaborative, and meaningful learning atmosphere. Students become more involved in the learning process, are able to analyze problems with a critical approach, and show an increase in understanding of fiqh concepts. Although some students initially had difficulty adapting to the independent learning method, support and guidance from teachers were very helpful in overcoming these obstacles.